Socially Different Student’s Self-Concept And Self-Efficiency In Relation To Their Locus of Control: A Review - Brar, Gursangeet (Innovative Research Thoughts, 2017)
People are born with a distinct personality that is generated by a number of internal and external influences that originate from the surrounding environment. As a person grows from birth through old age, these elements have a role in their physical, emotional, intellectual, and spiritual development. It is possible for a person's personality to represent their distinct qualities, such as their temperamental and emotional condition, as well as their nature. We encounter a wide range of people in our daily lives, each with their own unique set of personality traits. “A group of individuals who are confident, optimistic, risk-takers, and patient may be seen in the immediate surroundings. People with personality traits such as shyness, pessimism, impatience, and emotionality are also present in inverse proportions to the general population.